A molecular simulation approach towards the development of universal nanocarriers by studying the pH- and electrostatic-driven changes in the dynamic structure of albumin. Issue 23 (2nd April 2020) - Srivastav, Amit Kumar; Gupta, Sanjeev K.; Kumar, Umesh
Abstract : Role of pH and electrostatic charges on the conformations and dynamics of albumin structure by molecular dynamic study. Abstract : To explore the intramolecular interactions of protein, and its folding and unfolding mechanisms, we performed a simulation-based comparative study on albumin at different ionic strengths and pH. In this study, we performed molecular dynamics (MD) simulation for bovine serum albumin (BSA) at five different concentrations of NaCl (10, 20, 30, 40 and 50 mM), and five different pH values (2.0, 3.5, 4.3, 7.4, and 9.0). Herein, our aim was to unravel the effects of both pH and ionic strength on the conformations of the serum albumin structure. Our results indicate the effects of physicochemical factors in promoting conformational changes in the albumin structure, unlocking the hydrophobic sequences for hydrophobic drug binding. The BSA structure showed similarity to its native state in the pH range of 4.5 to 7.4 and at various ionic concentrations of NaCl. In the pH range of 3.5 to 4.5, the BSA structure showed denaturation in a controlled manner, which caused significant conformational changes in the molecular position of its hydrophobic amino acid residues. The resultant 3D structure gives insight into the amino acid trajectories. High denaturation and unstable behavior in the structural and conformational changes of the protein structure were observed at pH 2.0 and pH 9.0. We believe that these results and conditions will be helpful in the development of protein-based universal nanocarriers for the encapsulation of both hydrophilic and hydrophobic drugs.